Application of the DEMATEL Method in Analyzing Citizen-Centric Development Strategies in Public Administration (Case Study: Zanjan Municipality) - Babaei, Moghtada; Rahmani, Zain Alabedin; Jafari, Mostafa (Management Strategies and Engineering Sciences, 2024)
Citizen-centric public administration enhances active citizen participation in decision-making processes. It encourages citizens to share their opinions, ideas, and feedback on policies and programs. Promoting citizen-centricity in municipalities can highlight the importance of civic education and capacity-building initiatives. Municipalities provide opportunities for residents to enhance their understanding of local governance processes, rights, and responsibilities. The purpose of this study was to identify and examine the influence and impact of citizen-centric development strategies in public administration. This research is applied in terms of its purpose and falls within the category of mixed-method research using a deductive-inductive approach. The qualitative segment of the study involved professors and experts in policy-making, public management, and urban management. A purposive sampling method with the snowball technique was employed, resulting in a sample size of 17 participants. The quantitative segment included managers and staff of Zanjan Municipality. Using a non-probability convenience sampling method, 52 managers participated in the study. In the qualitative section, data from the interviews led to the identification of 10 citizen-centric development strategies in public administration. The quantitative analysis was conducted using the DEMATEL method. According to the DEMATEL analysis, networking, participation mechanisms, and citizen empowerment are both highly influential and highly influenced strategies. Fluid bureaucracies, evidence-based decision-making, and professional competencies of agents are the most impactful strategies. Additionally, effective technologies, participation mechanisms, and open information are more susceptible to influence compared to other strategies.